Base station assisted relay selection in device-to-device communications. (28th January 2020) - Khwakhali, Ushik Shrestha; Suksompong, Prapun; Gordon, Steven
The performance of cooperative cellular networks can be enhanced by using social information of users in the network. This paper presents a social-aware midpoint relay selection scheme that increases average throughput of D2D communication between users in the network leveraging social trust among nodes while selecting a relay node. The selection of a relay node is such that it has strong social link with the source and also located near to the midpoint of the distance between the source and the destination. Calculation of average throughput via simulation shows that our proposed scheme outperforms existing hybrid relay selection scheme by Pan and Wang by upto 14%. In addition, our proposed introduction of probe limit and wise selection of social threshold value can further enhance the throughput when social trust among nodes are high.